Tindak Tutur Lokusi Anak dalam Video YouTube ODG: “Are You A Rich Kid?” Kids Answer - Isnaeny Aplia Sutiarto; Rastya Ismatriyana; Hima R.D.P. Mahendra; Jayanti Megasari (Universitas Gadjah Mada, 2021)
This research is a pragmatic research with the discussion of Korean speech acts. The object of this research is the speech of children aged 14 years in the video